Từng bước nói tiếng Anh lưu loát. Tập 1 - Allen, Christopher B. (2011)
Vol 1 Part 1: Greetings & Introductions Act 1 Act 2 Scene 3 Scene 5 Act 3: Let's Review Act 4: Let's Practice Part 2: Countries & Nationalities Act 2 Scene 3 Scene 5 Act 3: Let's Review Act 4: Let's Practice The Summary